Children and childhood in American religions - Browning, Don S.; Miller-McLemore, Bonnie J.; Bartkowski, John P.; Bendroth, Margaret Lamberts; Beste, Jennifer; Bucko, Raymond; Buss, Emily; Dollahite, David; Dorff, Elliot; Ellison, Christopher G.; Gross, Rita; Ironcloud, Roger; et al. (Rutgers series in childhood studies., 2009)
Whether First Communion or bar mitzvah, religious traditions play a central role in the lives of many American children. In this collection of essays, leading scholars reveal for the first time how various religions interpret, reconstruct, and mediate their traditions to help guide children and their parents in navigating the opportunities and challenges of American life. The book examines ten religions, among other topics:. * How the Catholic Church confronts the tension between its teachings about children and actual practice. * The Oglala Lakota's struggle to preserve their spiritual tradit.